Analisis Pengaruh Pendapat Audit, Perubahan Kepemimpinan, Krisis Keuangan Terhadap Pergantian Auditor Pada Perusahaan F&B - Fannya Mutiara Sari; Henitha Nadia Kristy; Irda Agustin Kustiwi (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
The aim of this research is to analyze the influence of audit opinions, changes in leadership, and the financial crisis on the decision to change auditors in companies in the consumer goods industry sector listed on the Indonesia Stock Exchange in the period 2018-2022. Auditor turnover, or auditor turnover, has become an important phenomenon in the accounting and auditing literature because it can reflect the complexity of the relationship between the company, the auditor, and external factors. The research methodology used a quantitative approach with a sample consisting of companies in the consumer goods industry sector that experienced a change of auditor during the research period. Data collection comes from annual financial reports, audit reports, and announcements of auditor changes. Logistic regression analysis was used to test the research hypothesis. The desired hope from the research results is to introduce the factors that influence the decision to change auditors in the consumer goods industry sector. The practical implications of this research can help regulatory authorities, company management, and the audit profession in identifying potential risks that may be associated with changing auditors.